Relaciones hídricas en procedencias de QUERCUS SUBER L. - Castro, L; Aranda, I; Gil, L; Pardos, J A (III Congreso Forestal Español Congreso, 2001)
Response to drought was studied in 5 provenances of cork oak, which are representative of the ecogeographic range of the species. The variation of several water parameters was analysed in 2000 from the beginning of the summer to the first rainy period. Predawn water potential (ψama) was measured on 5 dates on 6 plants per provenance. On the same plants, pressure-volume curves were carried out on twigs from the spring flushing. Several parameters related to responses to drought were estimated: osmotic potential at full turgor (ψπ 100) and at the loss turgor point (ψπ 0), relative water content at zero turgor (CHR0) and elastic modulus at maximum turgor (εmax). Afterwards osmotic and elastic adjustments were evaluated, and the response to drought was separated of the influence of other factor such as phenology. When the water parameters were analysed, there were not significant differences among provenances, meanwhile the differences among dates were highly significant. A decrease in ψπ 100 and an increase of tissue rigidity (εmax) were observed during the period of water stress. The response to drought overlapped with variations due to ontogenic factors.
Keywords: Cork oak; osmotic adjustment; pressure-volume curves; water potential